Human leukocytes differentially express endocannabinoid-glycerol lipases and hydrolyze 2-arachidonoyl-glycerol and its metabolites from the 15-lipoxygenase and cyclooxygenase pathways. Issue 6 (26th September 2019) - Turcotte, Caroline; Dumais, Élizabeth; Archambault, Anne-Sophie; Martin, Cyril; Blanchet, Marie-Renée; Bissonnette, Élyse; Boulet, Louis-Philippe; Laviolette, Michel; Di Marzo, Vincenzo; Flamand, Nicolas
Abstract: 2-Arachidonoyl-glycerol (2-AG) is an endocannabinoid with anti-inflammatory properties. Blocking 2-AG hydrolysis to enhance CB2 signaling has proven effective in mouse models of inflammation. However, the expression of 2-AG lipases has never been thoroughly investigated in human leukocytes. Herein, we investigated the expression of seven 2-AG hydrolases by human blood leukocytes and alveolar macrophages (AMs) and found the following protein expression pattern: monoacylglycerol (MAG lipase; eosinophils, AMs, monocytes), carboxylesterase (CES1; monocytes, AMs), palmitoyl-protein thioesterase (PPT1; AMs), α/β-hydrolase domain (ABHD6; mainly AMs), ABHD12 (all), ABHD16A (all), and LYPLA2 (lysophospholipase 2; monocytes, lymphocytes, AMs). We next found that all leukocytes could hydrolyze 2-AG and its metabolites derived from cyclooxygenase-2 (prostaglandin E2 -glycerol [PGE2 -G]) and the 15-lipoxygenase (15-hydroxy-eicosatetraenoyl-glycerol [15-HETE-G]). Neutrophils and eosinophils were consistently better at hydrolyzing 2-AG and its metabolites than monocytes and lymphocytes. Moreover, the efficacy of leukocytes to hydrolyze 2-AG and its metabolites was 2-AG ≥ 15-HETE-G >> PGE2 -G for each leukocyte. Using the inhibitors methylarachidonoyl-fluorophosphonate (MAFP), 4-nitrophenyl-4-(dibenzo[d][1, 3]dioxol-5-yl(hydroxy)methyl)piperidine-1-carboxylate (JZL184), Palmostatin B, 4′-carbamoylbiphenyl-4-yl methyl(3-(pyridin-4-yl)benzyl)carbamate, N-methyl-N-[[3-(4-pyridinyl)phenyl]methyl]-4′-(aminocarbonyl)[1, 1′-biphenyl]-4-yl ester carbamic acid (WWL70), 4′-[[[methyl[[3-(4-pyridinyl)phenyl]methyl]amino]carbonyl]oxy]-[1, 1′-biphenyl]-4-carboxylic acid, ethyl ester (WWL113), tetrahydrolipstatin, and ML349, we could not pinpoint a specific hydrolase responsible for the hydrolysis of 2-AG, PGE2 -G, and 15-HETE-G by these leukocytes. Furthermore, JZL184, a selective MAG lipase inhibitor, blocked the hydrolysis of 2-AG, PGE2 -G, and 15-HETE-G by neutrophils and the hydrolysis of PGE2 -G and 15-HETE-G by lymphocytes, two cell types with limited/no MAG lipase. Using an activity-based protein profiling (ABPP) probe to label hydrolases in leukocytes, we found that they express many MAFP-sensitive hydrolases and an unknown JZL184-sensitive hydrolase of ∼52 kDa. Altogether, our results indicate that human leukocytes are experts at hydrolyzing 2-AG and its metabolites via multiple lipases and probably via a yet-to-be characterized 52 kDa hydrolase. Blocking 2-AG hydrolysis in humans will likely abrogate the ability of human leukocytes to degrade 2-AG and its metabolites and increase their anti-inflammatory effects in vivo. Graphical Abstract: Human leukocytes express several 2-arachidonoyl-glycerol lipases and efficiently hydrolyze 2-arachidonoyl-glycerol and its metabolites from the COX-2 and 15-LO pathways.